Mental Status of Older Adults: An Overview - Utami, Indah Amelia; Suarni; Silwanah, A. Sani (Bantayang Omni Cendekia, 2024)
Background: The older adults experience a decline in the ability of the body to adjust to the environment, which causes disturbances in their mental health and emotional well-being. World Health Organization showed the problem of mental disorders affecting 20 million people worldwide. The elderly are 2-3 times more likely to experience mental disorders caused by preventable physical illnesses. Objective: This study aimed to know the overview of elderly mental status in a public health center in Makassar. Methods: This study was descriptive study. The population in the study was the elderly in one of public health centers in Makassar. The total sample of this study was 86 respondents selected using purposive sampling. Results: This study showed that of 86 respondents, most respondents did not experience depression, amounting 71 (82.6%) respondents and majority of respondents experienced mild dementia, accounting for 63 (73.3%) respondents. Conclusion: Most elderly did not experience depression and suffered from mild dementia. It is expected for the elderly to always maintain social activities such as participating in elderly integrated health center activities held by public health center or elderly gymnastics which are routinely carried out every week in order to avoid depression and dementia.